Insider trading, costly monitoring, and managerial incentives - Noe, T; Hu, J (2001)
We derive conditions under which permitting manager “insiders” to trade on personal account increases the equilibrium level of output and the welfare of shareholders. These increases are produced by two effects of insider trading. First, insider trading impounds information about hidden managerial actions into asset prices. This impounding of information allows shareholders to make better personal portfolio-allocation decisions. Second, allowing insider trading can induce managers to increase, on average, the correlation between their personal wealth and firm value beyond the level dictated by the employment relationship alone. This increased correlation increases managerial incentives. When these two effects are only weakly present, permitting insider trading harms shareholders, because insider trading reduces shareholder control over the performance–compensation relationship. In addition, when managerial effort incentives are high and corporate governance costs are low, managers may prefer insider-trading restrictions because such restrictions force shareholders to offer them a larger fraction of output through the employment relationship.